GAMBARAN TINGKAT PENGETAHUAN PENGGUNAAN OBAT TRADISIONAL HIPERTENSI PADA PENDERITA HIPERTENSI DI KABUPATEN PELALAWAN PROVINSI RIAU - Husnawati, Husnawati; Sastrawati, Atriwida; Pratiwi, Erniza; Laia, Cindy Oktaviana (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2023)
Traditional medicine is an ingredient or ingredient in the form of plant material, animal material, mineral material, sarian preparation, or a mixture of these materials which have been used. One of the traditional treatments carried out by the community is for the treatment of hypertension. Knowledge is the result of knowing and occurs after someone has sensed a certain object. This study aims to describe the level of knowledge of the use of traditional hypertension drugs in patients with hypertension. The benefits of this study are to know the level of knowledge of hypertension sufferers in using traditional hypertension drugs. The design in this study was an observational study with descriptive methods. The sample was selected using purposive sampling technique. Data collection wasdone by using a questionnaire. Based on the results of the study, it was found that the description of the level of knowledge of respondents in using traditional hypertension medicine was generally categorized as good, namely as many as 77 respondents, the level of knowledge of respondents in the sufficient category as many as 20 respondents and as many as 3 respondents had a low level of knowledge.